PENGEMBANGAN MODUL PEMBELAJARAN GEOGRAFI BERBASIS PEDULI LIGKUNGAN UNTUK MENINGKATKAN SIKAP PEDULI LINGKUNGAN SISWA PADA MATERI SUMBER DAYA ALAM DI KELAS XI IPS SMA BINA UTAMA PONTIANAK - Novita Sariani; Chatarina Muryani; mohammad Gamal Rindarjono (Universitas Sebelas Maret (UNS), 2017)
ABSTRACTThis study aims to: (1) Determine the requirement in the use of character-based geography learning module at XI IPS SMA BinaUtama Pontianak, (2) Describe the steps of character-based geography learning module development in natural resource subject at XI IPS SMA Bina Utama Pontianak, (3) Identify the eligibility of the use of character-based geography learning module in the main subject of natural resource at XI IPS SMA Bina Utama Pontianak, and (4) Find out the improvement of environmental care attitude of students at SMA BinaUtama Pontianak after using the character-based geography module.Type of the study is research and development (R&D). Stages of R&D used are according to Borg and Gall’s theory with modification within four stages which are preliminary, arrangement, validation, and testing of product. Subject of the study is students of XI IPS SMA Bina Utama Pontianak 2016/2017 period with total of 42 students. Data collection techniques used are interview, questionnaire, and documentation methods, while data analysis techniques used are product moment and percentage formula.Results of the study show that: (1) From the analysis of the requirement in the use of character-based geography learning module at XI IPS SMA Bina Utama Pontianak, it is obtained a percentage of 80.92%. (2) The development of the design used in accordance with Borg and Gall’s theory within 4 stages is modified regarding the stages which are preliminary, development, validation, and testing stages.Structure of learning module presented consists of three parts: a. Introduction: cover, preface, table of contents, instructions, competence standard,basic competence, learning objectives, concept map; b. Contents: subtitle, learning objectives, complete subject description, do you know, formative tests, summary; and c. Final part: key answers, glossary, bibliography, author’s curriculum vitae, character refinement. (3) The average of the eligibility of development product at all stages is that the assessment of validation stage by the experts obtains 77.93% with very valid criteria,and the assessment of small-scale testing stage obtains very decent criteria. At all stages, it obtains an excellent category. (4) The attitude of environmental care before the use of character-based geography learning module is 63.30% andafter the use of character-based geography learning module is 85.17%. Thus, the use of characterbased geography learning module could improve the environmental care attitude of students.Keywords: Module, Character-Based, Attitude, Environmental Care